Aristotle’s Socratic Peirastic - Mombello, Eduardo H. (Revista Archai, 2025)
The aim of this essay is to present a strai-ghtforward interpretation of some main passages where Aristotle reveals what he understands by πειραστική. Usually interpreters believe his inspiration has drawn from the philosophical profile of Socrates and its elenchus. Faced with a number of difficulties presented by influential views, I argue that there are no reason to believe that Aristotle would have distinguished peirastic from dialectic neither by the figures of their syllogisms nor because their starting points have a different nature of the endoxa. By contrast, I defend the thesis that peirastic can be seen as a certain kind of expert knowledge that in practice becomes manifest as a successful refutation moment of the philosophically applied dialectic; at that moment the dialectic stricto sensu becomes reluctant to change the course of search for the principles of expert knowledge, insofar as such a movement would be a change in the direction posed by the sophistical threat of apparent wisdom on a given subject. I try to show how part of the – in Aristotle’s view – dialectical activity of Socrates fits in with various requirements of their inferential art of Topics. I suggest that this does not mean that Aristotle has built the peirastic on Socratic elenchus, but that he has used part of Socrates’ activity as philosophical evidence for his own fundamental dialectical conceptions.